TERPENOIDS AND STEROLS OF PEROVSKIA KUDRJASCHEVII ROOTS (Scientific journal of the Fergana State University, 2026)
The component composition of Perovskia kudrjaschevii (Lamiacaeae) roots collected during the period of dying off of the aboveground part in the territory of Bostandyk district of Tashkent region was studied. Oleanolic acid 3-acetate, ferruginol, stigmasterol, β-sitosterol, and oleanolic acid were isolated and identified for the first time from the gasoline fraction of the methanol extract of the plant roots. The isolated compounds were identified by studying the data of UV, 1H and 13C NMR spectra, as well as by direct comparison with authentic samples of substances.